2011
DOI: 10.1097/meg.0b013e32834d173c
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of HCV infection in Poland

Abstract: Prevalence of anti-HCV in the Polish population studied was up to 1.9%, but active infection could be diagnosed in only 31% of them. Intravenous drug use, blood transfusions before 1992, multiple hospitalizations, and male sex increase the risk of HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
2
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 18 publications
5
54
2
5
Order By: Relevance
“…Many other studies also found the same in different countries [3][4][5][6] . It is reassuring that HCV seroprevalence was only 0.2% in pregnant (young) Malian women [1] , possibly indicating that hygiene improved in healthcare facilities over time.…”
Section: Field Of Visionmentioning
confidence: 53%
“…Many other studies also found the same in different countries [3][4][5][6] . It is reassuring that HCV seroprevalence was only 0.2% in pregnant (young) Malian women [1] , possibly indicating that hygiene improved in healthcare facilities over time.…”
Section: Field Of Visionmentioning
confidence: 53%
“…16,17 Studies conducted in Poland have reported hepatitis C infection positivity of 0.5% among blood donors, 2.2% in pregnant women from Mazowsze region, and 70% in intravenous drug users. 16 The prevalence of HCV infection among participants of an annual meeting of the Polish Association of Orthopaedic Surgeons was 1.0%, and 1.3e1.4% among cohorts of HCWs representing different job categories.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted with immigrants in Sicily, Tramuto et al (2011) found a 4.0% positivity rate for anti-HCV (22/393). Thornton et al (2011) found an average prevalence of 0.5 to 1.2% in Ireland, with a strong association (80%) with drug use, and Flisiak et al (2011) also showed strong association with drug use and male gender in Poland. Mohtasham et al (2007) found a 45.4% prevalence in injected drug user inmates in Iran, and Mahfoud et al (2010) found a prevalence of 3.4% in prisoners in Lebanon, with strong associations with injected drug use and tattoos.…”
Section: Discussionmentioning
confidence: 99%